Faktor-Faktor yang Mempengaruhi Produksi Semangka di Kecamatan Lape, Kabupaten Sumbawa - Sulastri, Endang; Wijayanti, Nila; ZA, M. Aries; Wartiningsih, Alia; Hartono, Yadi (MuJAgri: Musamus Journal of Agribusiness, 2024)
This research aims to analyze the influence of independent variables, namely land area, seeds, labor, fertilizer, and pesticides, on watermelon production in Labuhan Kuris Village, Lape District. Additionally, the study tests the coefficient of determination to assess how much these variables influence watermelon production. The method used is purposive sampling, involving 30 watermelon farmers as respondents. Data collection techniques include observation, interviews, questionnaires, and documentation. The analysis was conducted using multiple regression. The results show that, partially, only the land area variable has a significant effect on watermelon production, while seeds, labor, fertilizer, and pesticides do not have a significant impact. However, simultaneously, all five independent variables significantly influence watermelon production. These findings indicate that land area is the primary factor in increasing watermelon production in the region.